2020
DOI: 10.3390/ma13071777
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Ability of Ferroelectric Oxide Nanowires Grown in Templates of Nanopores

Abstract: Nanowires of ferroelectric potassium niobate were grown by filling nanoporous templates of both side opened anodic aluminum oxide (AAO) through radiofrequency vacuum sputtering for multisensor fabrication. The precise geometrical ordering of the AAO matrix led to well defined single axis oriented wire-shaped material inside the pores. The sensing abilities of the samples were studied and analyzed in terms of piezoelectric and pyroelectric response and the results were compared for different length of the nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…The EDS spectrum of the filer of PVDF-TrFE/MWCNT in the AAO matrix is shown in Figure 2d. The results are in good agreement with the successfully reported piezoelectric oxide nanowire formation using template-assisted growth and non-chemical methods of synthesis [33].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The EDS spectrum of the filer of PVDF-TrFE/MWCNT in the AAO matrix is shown in Figure 2d. The results are in good agreement with the successfully reported piezoelectric oxide nanowire formation using template-assisted growth and non-chemical methods of synthesis [33].…”
Section: Resultssupporting
confidence: 90%
“…Further investigation is needed to establish the quantitative relationships between the nanotubes' array geometry and the performance of the PVDF-TrFE/MWCNT composite. Based on a previous investigation of a vacuum-sputtered potassium niobate ceramic material that filled the nanopores of anodic aluminum oxide [33], it can be concluded that the aspect ratio of the nanoformations is of great importance for the optimization of the piezoelectric yield. It was demonstrated in [38] that the piezoelectric voltage increased with the length of the KNbO 3 nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…The Bragg peaks of both samples were identified as belonging to an orthorhombically distorted perovskite structure ( Pbnm space group symmetry), in agreement with the data reported in the literature . The peak at 2θ ≅ 33° has a stronger intensity compared to the other peaks, which means that the AAO hard template promotes the formation of highly crystalline NTs oriented along a specific direction, as reported previously. , These XRD results also suggest no reaction between the AAO membrane and the NdNiO 3 oxide when the samples have been treated at 700 °C in an O 2 environment at atmospheric pressure.…”
Section: Resultssupporting
confidence: 83%
“…51 The peak at 2θ ≅ 33°has a stronger intensity compared to the other peaks, which means that the AAO hard template promotes the formation of highly crystalline NTs oriented along a specific direction, as reported previously. 52,53 These XRD results also suggest no reaction between the AAO membrane and the NdNiO 3 oxide when the samples have been treated at 700 °C in an O 2 environment at atmospheric pressure.…”
Section: Resultsmentioning
confidence: 73%
“…Solid electrolyte gas sensors, electrochemical gas sensors, metal oxide semiconductor sensors (MOS), catalytic combustion gas sensors, and other types of gas sensors have been documented in the literature [14][15][16][17]. MOS type sensors are among the most researched of the many types of gas sensors because they may be used to detect a variety of gases at lower concentrations merely by studying the change in resistance induced by the interaction between the sensing material and the target gas [18][19][20][21]. The operating concept of a gas sensor is based on changes in the sensing material's electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%